PENYULUHAN KESEHATAN DAN PEMERIKSAAN LABORATORIUM KELOMPOK LANSIA BANJAR MUMBUL, BENOA, KUTA SELATAN, BADUNG OLEH FAKULTAS KEDOKTERAN UNIVERSITAS MAHASARASWATI DENPASAR SEBAGAI WUJUD PENGABDIAN KEPADA MASYARAKAT - Sumawirawan, I Made; Widiasa, Aa Made; Novitasari, Novitasari; Bistara, Rendra Wisnu; Pramesti, Aa Intan (LP2M STP Mataram, 2024)
Health counseling has been conducted in the elderly group in Banjar Mumbul, Benoa, South Kuta, Badung, Bali. Health counseling on medication compliance, herbal plants for treatment, hypercholesterolemia and hypertension and laboratory examinations were carried out twice, in April and June 2024. There was a very significant improvement in blood pressure, medication compliance, blood sugar and cholesterol test results in the elderly group of our partners. Pre- and post-test laboratory examinations were carried out, as well as assessment of medication compliance using a questionnaire. We concluded that this counseling was successful in improving the health of the community, especially in the elderly group of Banjar Mumbul, Benoa, South Kuta, Badung, Bali.